CATHOLIC POLITICAL DOCTRINE DURING THE WORLD WARS - G. T. Sardaryan (Vestnik MGIMO-Universiteta)
The subject of the study is the perception of political ideologies, movements and parties development problems by the Catholic Church, during the period of the First and Second World War. The object of the study is the Catholic political doctrine during the pontificate of Benedict XV, Pius XI and Pius XII. The author pays special attention to the key encyclical – Quadragesimo Anno, published in the 40th year after Rerum Novarum, as well as the influence that the Church has had on the formation of the post-war political system of European countries. Such methods as dialectical, logical, comparative, systemic, and a number of others are widely used in the article. The main conclusion of the author is that during the world wars the Church did not concentrate political doctrine only around foreign policy issues, being in search of a political platform capable of ensuring the implementation of its principles within the political process. Obviously, neither liberalism, nor communism could be such. Moreover, it was precisely because of the emergence of the communist threat that the Catholic Church perceived a number of authoritarian regimes in the early years of their existence as subjects that could be oriented toward a less hostile direction of development. As a result, Pius XII, choosing between existing political ideologies, did not stake on any of them, preferring the choice of a political regime - democracy.